Pembuatan Hydroxyapatite Dari Limbah Cangkang Telur Bebek Menggunakan Metode Sol Gel Dengan Pelarut Asam Nitrat - Nadilla Jelsi Noviyana (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This study aims to determine the effect of nitric acid concentration and stirring speed on the Ca/P molar ratio through the formation of Precipitated Calcium Carbonate (PCC) from duck eggshells and to analyze the size and shape of hydroxyapatite crystals. Duck eggshell waste from Jl. Mojosari, Sumbersuko District, Lumajang Regency, was used as the raw material. The research process consisted of three stages: (1) Calcination of eggshells, (2) Synthesis of PCC by dissolving duck eggshells in 2 M HNO₃, and (3) Synthesis of hydroxyapatite by mixing PCC with (NH₄)₂HPO₄ at pH 9. The results showed that (1) Nitric acid concentration affects the Ca/P molar ratio, where a higher nitric acid concentration leads to a lower Ca/P molar ratio, with a Ca/P molar ratio of 4.1599 at a concentration of 0.6 M and a stirring speed of 500 rpm, (2) Stirring speed also affects the Ca/P molar ratio, where a higher stirring speed results in a lower Ca/P molar ratio, and (3) The hydroxyapatite crystal size under these conditions was 116.3322 nm, with a rough crystal surface.